Public Perception On Application Use E Tokopedia Commerce Towards Inside Ease Get Goods - Siregar, Aldio Azani; Nasution, Muhammad Irwan Padli; Sundari, Sri Suci Ayu (Bina Bangsa International Journal of Business and Management, 2024)
The progress of the times leads us to evolve, whether we like it or not we have to follow the flow of civilization of the times. With the times, technology is also growing, from when we wake up until we go to sleep again, technology always accompanies us every day. With the growth of technology, more and more new creations are found. With the existence of internet technology, we can get information quickly and easily. Starting from any news or event to any purchase can be done online. As with ordinary shops in the real world, it turns out that the way to buy and sell transactions online is just as easy, even easier and more profitable. This study discusses the use of the online trading site and application tokopedia.co.id. The most monthly e-commerce web visitors in the first quarter of 2021 were Tokopedia, 135 million visits. The following data shows that the use of the Tokopedia application is very large based on consumer trust, who believe that buying through the Tokopedia e- commerce is easier to get the desired item. The method used in writing this scientific paper uses the case study method, where the case study data can be obtained from all interested parties, in other words, in this research it is collected from various sources. The purpose of this study was to determine the perception of using the Tokopedia e-commerce application on the ease of consumption of goods so that shopping satisfaction and shopping convenience.